Antimicrobial potential and secondary metabolites of isolated bacteria from marine sediments in Gigantes Islang, Iloilo against S. aureus, E. coli, and C. tropicalis - BJ4 D. Castro, Leslie E. Traqueña 4 0 16; 5
ABSTRACT: Antimicrobial resistance (AMR) is a serious public health concern as it progresses globally which soon might negate the ability of the community to treat infectious diseases. Bioactive compounds present in marine habitat holds an auspicious source of natural products that can be potential in inhibiting microbial growth. This study aimed to observe the antimicrobial potential and secondary metabolites of bacterial isolates from marine Sediment in Gigantes Island, Iloilo against Staphylococcus aureus, Escherichia coli, and Candida tropicalis. There were four bacterial isolates that have been cultured from marine sediment sample-all of them belong to Class Bacilli: Cytobacillus kochii, Cytobacillus firmus, Bacillus amyloliquefaciens, and Mammaliicoccus sciuri. The bioactive compound of each bacterial isolate did not exhibit a zone of inhibition to any of the test organisms. The secondary metabolites in broth ethyl acetate of each bacterial isolate from marine sediment were screened by Thin Layer Chromatography; there are no secondary metabolites detected in TLC. However negative, this study serves as a starting line for future studies on marine-derived bioactive compounds. Keywords: Antimicrobial Resistance, Cytobacillus kochii, Cytobacillus firmus, Bacillus amyloliquefaciens, and Mammaliicoccus sciuri.
Undergraduate Thesis: (BS Biology major in Cellular and Molecular Biology) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2